How Social Support Impact Teachers’ Mental Health Literacy: A Chain Mediation Model - Li, Sihui; Sheng, Youyu; Jing, Yumei (Frontiers in Psychology, 2022)
Teachers have an important social role, and their mental health literacy is very important to their own abilities as educators and to the growth and development of those they educate. This study explored the mechanism underlying the influence of social support on teachers’ mental health literacy by conducting a questionnaire survey of 573 teachers. The results showed that social support can influence teachers’ mental health literacy not only through the separate effects of life satisfaction and coping tendency but also through the chain mediation effect of life satisfaction and coping tendency; however, the direct effect of social support on the teachers’ mental health literacy is not significant. This study is conducive to understanding the internal mechanism underlying the relationship between social support and mental health literacy. It reminded us that when formulating mental health literacy promotion programs for teachers, we should not only provide adequate social support to improve but also should pay attention to improvements in their coping tendencies and life satisfaction.